Efficiency of human capital use in agriculture at the present stage of development (Journal of Economic Research & Business Administration, 2018)
The article presents the results of theoretical review and materials generalization on the interpretationof human capital essence and it’s role. It is the main strategic resource capable of solvingcomplex problems of the country’s transition to a «green economy». Human capital is considered byus as a set of certain personal, social, professional, business qualities, and is an important investmentresource, the use of which contributes to the improvement of production efficiency. Considerableattention is paid to methodological aspects of human capital research. Despite the importance ofproductive use problem of human capital, the interrelationship of quality, personnel motivation andefficiency of its use is insufficiently researched, which caused the need for a more detailed researchof this issue with the use of selective, monographic studies, statistical methods of researching stochasticconnections. The research includes the following stages: analysis and assessment the level of human capital development in Kazakhstan against the background of developed foreign countries,identificate the factors affecting the use of this capital and the calculation of their relationshipstrength; formation of proposals for the accumulation, effective use and further human capital developmentin the agricultural sector.